Termite Infestation Associated with Type of Soil in Pulau Pinang, Malaysia (Isoptera: Rhinotermitidae) - Abdul Hafiz Ab Majid; Abu Hassan Ahmad (Tropical Life Sciences Research, 2013)
Nine soil samples from nine buildings infested with Coptotermes gestroi in Pulau Pinang, Malaysia, were tested for the type of soil texture. The soil texture analysis procedures used the hydrometer method. Four of nine buildings (44%) yielded loamy sand-type soil, whereas five of nine buildings (56%) contained sandy loam-type soil. Sembilan sampel tanah dari sembilan bangunan yang diserang oleh Coptotermes gestroi di Pulau Pinang, Malaysia, telah diuji untuk menentukan jenis tekstur tanah. Prosedur analisis tekstur tanah menggunakan kaedah hidrometer. Empat daripada sembilan bangunan (44%) dikenal pasti sebgai tanah jenis liat pasir. Manakala lima daripada sembilan bangunan (56%) telah dikenal pasti sebagai tanah jenis gembur berpasir.